Examining how teachers’ characteristics impact student motivation and achievement across subject, school level, gender, and prior achievement level - Shin, Dajung Diane; Park, Seohee; Kim, Ju Ae; Nagengast, Benjamin; Bong, Mimi (Social psychology of education, 2025)
Teachers’ characteristics can significantly influence the quality of student functioning. Yet, there has been little exploration regarding which attributes matter to which outcomes, and for whom, and under what conditions. In this study, we considered four characteristics as perceived by students, namely competence, student-centered instruction, closeness with students, and enthusiasm, and examined how they predicted students’ self-efficacy, interest, and achievement. We also tested whether the predictive relationship differed by subject area (Korean vs. math), school level (middle school vs. high school), gender, and prior achievement. To address these questions, data from the Gyeonggi Educational Panel Study 2012 (GEPS 2012), which included responses from over 5,500 students in Grades 7 to 12, was subjected to two-level regression analyses. The results showed that the considered characteristics made significant differences in students’ motivation and achievement across subjects and school levels, both independently and by interacting with the gender and prior achievement of students, even after controlling for their prior scores. More specifically, teachers perceived to be competent and relatable benefited all students across different contexts, although high-achieving students tended to reap even greater benefits from them. However, teachers’ implementation of student-centered instructional strategies produced conflicting results as it enhanced the motivation of low-achieving students but hurt the achievement of high-achieving students. Our findings add to the existing literature on the effects of teacher characteristics and provide practical insights for teachers to tailor their support to diverse students in different learning contexts.